Parameter Optimization on Esterified Oil Palm Empty Fruit Bunch Cellulose (OPEFB) Pengoptimuman Parameter bagi Selulosa Tandan Kosong Kelapa Sawit (TKKS) Teresterifikasi - Mostapha, M. (Penerbit Universiti Kebangsaan Malaysia, 2021)
Chemical modifications of oil palm empty fruit bunch cellulose (OPEFBC) using ethylenediaminetetraacetic acid (EDTA) and acetic acid (AA) with different parameters were studied and optimized. At the initial stage, OPEFBC pulp was treated using four stages of bleaching stage (D-E-E-D) for production of OPEFBC. Next, the OPEFB cellulose undergo esterification process using AA and EDTA under microwave assisted heating system to further enhance esterification. The influence of pre-treatment parameters on thermal stability and functional group changes were optimized using central composite design (CCD), response surface modelling (RSM) followed by thermogravimetric analysis (TGA) and functional group analysis (FT-IR). The results showed there were significant differences occurred on the modified OPEFB cellulose particularly by EDTA where higher thermal properties were observed with better esterification product with higher modification occurs compared to cellulose treated with AA. The RSM data showed that temperature, time, and chemicals concentrations optimized for cellulose-AA were at 90°C, 46 min, and 8.18, respectively, while the optimum parameters for cellulose-EDTA were at 100°C, 70 min, and 0.7 concentrations, respectively. Based on CCD analysis, the results showed that OPEFBC cellulose esterified with EDTA agent is better than AA. © 2021 Penerbit Universiti Kebangsaan Malaysia. All rights reserved.